Economical basis to address micronutrient deficiencies in developing world - Hassan, Amirul (Indian Journal of Community Health, 2015)
Malnutrition has been called by economists at the World Bank as the “non-human face” of poverty,1 Adults who were malnourished as children earn at least 20% less on average than those who weren’t , 2.Malnutrition is often caused by underlying economics, i.e. the lack of money. Economics is very important in regards to malnutrition; it allows an individual to purchase nutrients. In many places around the world, a lack of money prevents the purchase of a variety of foods. The lack in variety usually leads to micronutrient malnutrition. Economics also decides the production of food in all countries around the world and the ability of a country to overcome difficult times. Thus economics affects ALL people at ALL levels of society, 3.Micronutrient deficiencies also known as ‘hidden hunger’ are determining and aggravating factors for health status and quality of life. It is estimated half of anaemia cases are due to iron deficiency , 4. Almost half of children in low- and middle-income countries – 47% of under-fives are affected by anaemia, impairing cognitive and physical development,5. Iodine deficiency is the greatest single cause of mental retardation and brain damage. Coincidently, the number of countries in which iodine-deficiency disorders were considered a public health concern reduced by 43% between 1993 and 2007,6. Zinc deficiency affects children’s health and physical growth; it is also essential for mothers during pregnancy. It is estimated to cause 4% of deaths in pre-school aged children in lower-income countries. 7 . The Global Burden of Disease estimates showed that among the 26 major risk factors of the global burden of disease,8 iron deficiency ranks ninth overall, zinc deficiency is eleventh, and vitamin A deficiency, is thirteenth. Annually each developing country of the world are losing over millions or billions US in Gross Domestic Product (GDP) to vitamins and minerals deficiencies. But scaling up core micronutrient intervention would cost few millions or one tenth of million. Not only this, the cost of core micronutrient interventions are as low as US 0.05-3.60 per person annually. Thus return on investment is as high as eight to thirty times the cost,9.